gamma-H2AX: Can it be established as a classical cancer prognostic factor? - Viktoria-Varvara Palla; Georgios Karaolanis; Ioannis Katafigiotis; Ioannis Anastasiou; Paul Patapis; Dimitrios Dimitroulis; Despoina Perrea (Tumor Biology)
Double-strand breaks are among the first procedures taking place in cancer formation and progression as a result of endogenic and exogenic factors. The histone variant H2AX undergoes phosphorylation at serine 139 due to double-strand breaks, and the gamma-H2AX is formatted as a result of genomic instability. The detection of gamma-H2AX can potentially serve as a biomarker for transformation of normal tissue to premalignant and consequently to malignant tissues. gamma-H2AX has already been investigated in a variety of cancer types, including breast, lung, colon, cervix, and ovary cancers. The prognostic value of gamma-H2AX is indicated in certain cancer types, such as breast or endometrial cancer, but further investigation is needed to establish gamma-H2AX as a prognostic marker. This review outlines the role of gamma-H2AX in cell cycle, and its formation as a result of DNA damage. We investigate the role of gamma-H2AX formation in several cancer types and its correlation with other prognostic factors, and we try to find out whether it fulfills the requirements for its establishment as a classical cancer prognostic factor.